2004
DOI: 10.1158/0008-5472.can-03-0476
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D, a Component of the Permeability Transition-Pore, Is an Apoptosis Repressor

Abstract: The permeability transition (PT)-pore is an important proapoptotic protein complex in mitochondria. Although it is activated by many signals for apoptosis induction, the role of its various subunits in cell death induction has remained largely unknown. We found that of its components, only the voltage-dependent anion channel in the outer mitochondrial membrane and the adenine nucleotide translocator-1 (ANT-1), a PT-pore subunit of the inner membrane, are apoptosis inducers. We also report that ANT-1's direct i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 71 publications
(72 reference statements)
7
84
0
Order By: Relevance
“…However, a substantial body of evidence indicates that cypD has anti-apoptotic activities. Importantly, we [120,121] and others [122] have recently found that enforced cypD expression can specifically repress the activation of the PT-pore. Another study in neuronal cells also observed apoptosis inhibition (but sensitisation for necrosis) by cypD overexpression [123].…”
Section: Overexpression Studies On Cypdmentioning
confidence: 57%
See 1 more Smart Citation
“…However, a substantial body of evidence indicates that cypD has anti-apoptotic activities. Importantly, we [120,121] and others [122] have recently found that enforced cypD expression can specifically repress the activation of the PT-pore. Another study in neuronal cells also observed apoptosis inhibition (but sensitisation for necrosis) by cypD overexpression [123].…”
Section: Overexpression Studies On Cypdmentioning
confidence: 57%
“…Moreover, there is accumulating evidence that cyclosporin A can induce apoptosis in certain cells [124][125][126][127]. In fact, the clinical use of CsA is still limited by its potential toxicity [128,129] and a specific inhibition of the PT-pore as observed with cypD [120,122] would be therapeutically of high interest. Hence, it is important to determine how overexpressed cypD induces or inhibits cell death.…”
Section: Overexpression Studies On Cypdmentioning
confidence: 99%
“…However, mouse knockout studies led to the conclusion that ANT would not (always) be required for apoptotic MOMP (Kokoszka et al, 2004). Recent evidence suggests that some ANT isoforms (ANT1, ANT3) are apoptogenic while others are not (ANT2) (Schubert and Grimm, 2004;Zamora et al, 2004). In 2005, a fourth ANT isoform (ANT4) has been identified in man (Dolce et al, 2005) and mouse (Rodic et al, 2005) by means of two independent experimental approaches.…”
Section: Mitochondrial Membrane Permeabilization: the Central Event Omentioning
confidence: 99%
“…14 By contrast, it has also been reported that in some instances cyclophilin D prevents apoptotic cell death through modulation of Bcl-2 and by promoting the binding of HKII to the mitochondria. 15,16 Shulga et al 12 demonstrated that a decrease of SIRT3 activity enhances the binding of HKII to the mitochondria by increasing cyclophilin D activity, potentially making the cells resistant to apoptosis.Apoptotic cell death is characterized by well-defined biochemical and morphological changes such as plasma membrane blebbing, DNA fragmentation and changes in the MPT with release of mitochondrial proteins. 17 Mitochondria have a central role in regulating the apoptotic process because many apoptogenic proteins such as cytochrome c,…”
mentioning
confidence: 99%
“…14 By contrast, it has also been reported that in some instances cyclophilin D prevents apoptotic cell death through modulation of Bcl-2 and by promoting the binding of HKII to the mitochondria. 15,16 Shulga et al 12 demonstrated that a decrease of SIRT3 activity enhances the binding of HKII to the mitochondria by increasing cyclophilin D activity, potentially making the cells resistant to apoptosis.…”
mentioning
confidence: 99%